Strengthening Digital Literacy And Business Law To Maximize The Potential Of Village Communities - Ibnu Rasyid Munthe; Novi Fitriandika Sari; Bhakti Helvi Rambe; Fauziah hanum; Nur’Ainun gulo; Ade trya amanda; Shabrina Rasyid Munthe (CV. AFDIFAL MAJU BERKAH, 2025)
Community service activities in Afdeling 1 Rantauprapat Village, which will be held in August 2025, aim to improve digital literacy skills, strengthen business legality, and optimize the potential of local assets to strengthen the community's economy. This program is implemented using the Asset-Based Community Development (ABCD) approach, which emphasizes the development of internal community strengths through the use of existing social, economic, and cultural assets. The activity process was carried out for one month by involving ten participants consisting of business actors, village officials, and students who acted as facilitators through the service-learning method. Activities include practical digital literacy training, business legality assistance through the Online Single Submission (OSS) system, and the establishment of a collaborative network between participants and related institutions. The results showed a significant increase in the participants' ability to utilize digital technology for product promotion and sales, with an average increase in turnover of 25% and a participation rate of 95%. In addition, this activity has a positive impact on increasing confidence, legal awareness, and women's active involvement in productive economic activities. The application of the ABCD method has proven effective in strengthening social solidarity, building trust between stakeholders, and creating empowerment models that can be replicated in other regions with similar socioeconomic characteristics.